Modified Hydrological Regime on Irrigation and Water Supply in Lake Areas: A Case Study of the Yangtze River–Dongting Lake - Fang, Juanjuan; Li, Yitian; Wang, Dong; Xie, Shuai (Frontiers in Earth Science, 2022)
Lake systems are of fundamental significance for the ecological environment and social development. Driven by climatic changes and human activities, the hydrological situation of rivers and lakes has been altered considerably, and directly affects the reliability of irrigation and water supply in lake areas. In the case of the Yangtze River–Dongting Lake area, the quasi-equilibrium of their hydrological states and water balance have been affected by the operation of the Three Gorges Project that has made irrigation and water supply across the lake area increasingly tense. Ever since, the available water supply in the Dongting Lake area has decreased during the months of September and October, and the overall water level in the lake area has dropped by 0.8–2.0 m. Although the total amount of water in the lake area is still above the water supply threshold, an obvious decreasing trend has been observed in the fulfillment of the demand for both irrigation and water supply in urban and rural regions. Additionally, the fulfillment of secured water supply and irrigation requirements has respectively dropped from 95% and 78% before the operation of the Three Gorges Project to 82% and 46% after it. Meanwhile, the total water shortage increased from 57.683 MCM to 143.607 MCM. By advancing or postponing impoundment schedules, the impact of the Three Gorges Reservoir on irrigation and water supply in the lake area during September and October can be alleviated, and the water supply capacity can be respectively increased by approximately 1.3% and 1.4%. The highlights of this study include the quantification of the impacts of the operation of large-scale water conservancy projects at the level at which the requirements on irrigation and water supply in the lake area are satisfied, and the prediction of the trends for future evolvement. In addition, corresponding strategies that provide a technical reference for the comprehensive regulation and control over water resources and the security of water supply in the river basin are discussed.